1984
DOI: 10.1111/j.1365-3059.1984.tb01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on metalaxyl‐resistant Phytophthora infestans in potato crops in south‐west Scotland

Abstract: In 1981 metalaxyl‐resistant Phytophthora infestans was found in 44% of the 63 crops examined in south‐west Scotland. In 1982, when fungicides containing acylalanines (metalaxyl or ofurace) were not used in the area, it was detected in 15%. Metalaxyl‐resistant strains were found in several crops which had been sprayed only with non‐acylalanine fungicides or had received no fungicidal treatment. In neither year was resistance associated with a significant breakdown of disease control. Metalaxyl‐resistant isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Other authors found that an in vitro method using agar media gave repeatable and reliable result with fast growing isolates and it was compatible with the leaf disc assay as well as with field experiments (Goodwin et al, 1996;Matuszak et al, 1994). Other authors have used a potato tuber disc method or detached leaf assay (Holmes and Channon, 1984;Kadish and Cohen, 1988b). For us,…”
Section: Discussionmentioning
confidence: 90%
“…Other authors found that an in vitro method using agar media gave repeatable and reliable result with fast growing isolates and it was compatible with the leaf disc assay as well as with field experiments (Goodwin et al, 1996;Matuszak et al, 1994). Other authors have used a potato tuber disc method or detached leaf assay (Holmes and Channon, 1984;Kadish and Cohen, 1988b). For us,…”
Section: Discussionmentioning
confidence: 90%
“…Phenylamides have been applied to potato crops in Scotland for more than 20 years and 44–60% of isolates collected in the mid‐ to late 1980s were resistant (Holmes & Channon, 1984; Bain & Holmes, 1990). The virtual absence of resistant A2 isolates was thus unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The A2 mating type was first reported in 1983 (Malcolmson, 1985) but, between 1985 and 1988, only six out of 145 isolates tested were A2 (SF Carnegie, SASA, Edinburgh, personal communication). Metalaxyl‐resistant isolates were recovered from 44% of crops in south‐west Scotland in 1981 (Holmes & Channon, 1984) and from almost 60% of tuber samples tested in a survey during 1988–89 (Bain & Holmes, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the first detection of strains of P. infestans resistant to phenylamides occurred in 1981, 3 years after these fungicides were registered (Cooke 1981;Holmes and Channon 1984). In the UK, phenylamides were only approved for late blight control in mixtures with mancozeb.…”
Section: Ukmentioning
confidence: 99%